The status of preschool teachers in two municipalities following the economic collapse - Axelsdóttir, Laufey; Pétursdóttir, Gyða Margrét (Veftímaritið Stjórnmál og stjórnsýsla, 2014)
This feminist study examines the working conditions of preschool teachers, a female dominated occupation, in two municipalities in Iceland and asks, in light of government policy, if and then how the municipalities facilitate preschool teachers professionalism following the 2008 bank collapse. Weber´s (2001) theoretical framework is applied to explore the professional status of the preschools and the impact of local government on preschool teachers’ position. Qualitative methods were used and data was gathered in 2011 and 2012. Thirteen interviews were conducted with women and men in two preschools and the schools administrative environment. Preschool teachers employed in management and non-management positions as well as assistants were interviewed. The study’s results show that financial cutbacks in local government affect preschool teachers and assistants and thus the position of women in the labour market by preserving their subordination. Furthermore, preschool children seem to be affected by the cutbacks which possibly have negative consequences on their well-being. Reforms and developments of the preschool teachers education seem to be met with considerable opposition from local government and more emphasis is placed on operational costs rather than strengthening the preschool teachers in their role as professionals. The results thus point to a gap between government policy and the municipalities’ local version of that same policy. Í greininni er staða leikskólakennarastarfsins, sem er hefðbundið kvennastarf, skoðuð í tveimur sveitarfélögum í kjölfar efnahagslegs samdráttar. Rannsóknin er femínísk og er kenningarlegum ramma Lynn Weber (2001) um samtvinnun mismunarbreyta beitt til að varpa ljósi á stöðu leikskólakennarastarfsins innan tveggja sveitarfélaga. Rannsóknaraðferðin var eigindleg en gagnasöfnun hófst í september 2011 og stóð fram í apríl 2012. Greinin byggir á þrettán viðtölum við konur og karla sem starfa í tveimur leikskólum og í ytra starfsumhverfi þeirra. Tekin voru viðtöl við ...